Octahedral Tilting in Homologous Perovskite Series CaMoO3-SrMoO3-BaMoO3 Probed by Temperature-Dependent EXAFS Spectroscopy - Bakradze, Georgijs; Kuzmin, Alexei (MDPI, 2022)
Local distortions in perovskites can be induced by cation displacements and/or by the tilting and rotating of cation–anion octahedra. Both phenomena have been subject to intense investigations over many years. However, there are still controversies in the results obtained from experimental techniques that are sensitive to long-range order (X-ray, neutron, or electron diffraction) and those sensitive to short-range order (X-ray absorption spectroscopy). In this study, we probed the details of the local environment in AMoO3 perovskites (A = Ca, Sr, Ba) using extended X-ray absorption fine structure (EXAFS) in a wide temperature range (10–300 K). An advanced analysis of the EXAFS spectra within the multiple-scattering formalism using the reverse Monte Carlo method enhanced by an evolutionary algorithm allowed us (i) to extract detailed information on metal–oxygen and metal–metal radial distribution functions, and metal–oxygen–metal and oxygen–metal–oxygen bond angle distribution functions, and (ii) to perform polyhedral analysis. The obtained results demonstrate the strong sensitivity of the EXAFS spectra to the tilting of [MoO6] octahedra induced by the differences in the sizes of alkaline earth metal cations (Ca2+, Sr2+, and Ba2+).
This research was funded by the State Education Development Agency project No. 1.1.1.2/VIAA/3/19/444 (agreement No. 1.1.1.2/16/I/001) realized at the Institute of Solid State Physics, University of Latvia; the Institute of Solid State Physics, University of Latvia, as the Center of Excellence received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; CaMoO3; SrMoO3; BaMoO3; perovskite; octahedral tilting; EXAFS spectroscopy; reverse Monte Carlo